2014
DOI: 10.3389/fphys.2014.00013
|View full text |Cite
|
Sign up to set email alerts
|

How man-made interference might cause gas bubble emboli in deep diving whales

Abstract: Recent cetacean mass strandings in close temporal and spatial association with sonar activity has raised the concern that anthropogenic sound may harm breath-hold diving marine mammals. Necropsy results of the stranded whales have shown evidence of bubbles in the tissues, similar to those in human divers suffering from decompression sickness (DCS). It has been proposed that changes in behavior or physiological responses during diving could increase tissue and blood N2 levels, thereby increasing DCS risk. Dive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Thus, fats have been considered 'slow' loading tissues because of assumed low perfusion and/or generally modest vascularization relative to 'essential' tissues (e.g. Zimmer and Tyack, 2007;Fahlman et al, 2009Fahlman et al, , 2014. However, recent studies have demonstrated that blood flow in diving marine animals may be more variable during different dive phases and conditions, such as elevated exercise and foraging/feeding (Zapol et al, 1979;Butler, 1982;Noren et al, 2012).…”
Section: Implications For Dive Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, fats have been considered 'slow' loading tissues because of assumed low perfusion and/or generally modest vascularization relative to 'essential' tissues (e.g. Zimmer and Tyack, 2007;Fahlman et al, 2009Fahlman et al, , 2014. However, recent studies have demonstrated that blood flow in diving marine animals may be more variable during different dive phases and conditions, such as elevated exercise and foraging/feeding (Zapol et al, 1979;Butler, 1982;Noren et al, 2012).…”
Section: Implications For Dive Modelsmentioning
confidence: 99%
“…In tissues, these bubbles can produce mechanical and biochemical problems, which can be fatal (reviewed in Vann et al, 2011). The occurrence of decompression sickness in air-breathing divers depends on the animal's diving regime (Fahlman et al, 2014). During a dive, tissues can become saturated or supersaturated with inert gases, such as nitrogen (N 2 ), and if ambient pressure decreases faster than the tissues can release the gas, decompression sickness can result (Boyle, 1670;Vann et al, 2011;Hooker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, no additional gas is taken up and the gas that was taken up in the intermediate region is now circulating between the blood and tissues (figure reproduced from Ref. [5]). may be at higher risk of forming bubbles.…”
Section: Figurementioning
confidence: 99%
“…For every 10 m of depth, the pressure increases by 1 ATA, and by measuring the pressure these instruments were able to record the depth to which the whales were diving while foraging, or hunting for food. We used the pressure data and the Gas Solubility to estimate the amount of gas the whales had dissolved in the blood and tissue, and these estimates gave us an idea of how likely the whales were to experience gas bubbles [4,5]. We compared these estimated values of dissolved gas based upon the whales' diving behavior before, during, and after exposure to sonar.…”
Section: A Complicated Life In the Dark!mentioning
confidence: 99%